Parental behavior and near screen use in childhood: a route to reduce screen induced myopia - Iyer, Vasanthi; Hermans, Roel; Polling, Jan Roelof; Klaver, Caroline; Reijneveld, Sijmen (Frontiers in Public Health, 2025)
IntroductionContinuous near work activities like near screen use contribute to the surge in myopia (near sight) prevalence, worldwide particularly among youth. Parental management skills play a crucial role in guiding children's use of digital screens. The aim of the study was to assess near screen use among children and to investigate the role of parental behavioral determinants in its management.MethodsWe conducted an online survey among 395 parents of 9–12-year-olds. We assessed behavioral determinants, components of the CASI-model (Communication Activation Strategic Instrument), near screen use, and parental management, including knowledge, attitude, risk-perception, self-efficacy and (influence of) social environment. We performed logistic regression with parental management skills as outcome, adjusted for parental educational level, age and sex of the child.ResultsOf the 395 9–12-year-olds, 78.7% had their own smart phone. Of these children, 26.0% spent more than 2 h a day on near screens at home. 75.1% of the parents had heard about myopia, of these 59.3% made a significant effort to reduce screen time (odds ratio, 95%-confidence interval: 2.62; 1.59–4.29). Only 28.1% of parents considered the risk of myopia due to handheld screen use to be high, and 62.6% of them spent relatively more efforts to minimize near screen time (1.32; 1.01–1.72). A more negative attitude of parents toward screens was associated with more efforts to reduce screen time (1.25; 1.17–1.35), as was a higher self-efficacy (1.08; 1.03–1.13). Surprisingly, a significant negative association was found between confidence in one's ability to reduce screen use and the efforts made (0.76; 0.58–0.99).ConclusionsParents' knowledge, attitude and self-efficacy relate to their management skills of screen use of children. Mass media campaigns targeting these determinants in parents could help to reduce the risks of myopia and associated complications later in life.